2000
DOI: 10.1128/iai.68.4.2043-2052.2000
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose 6,6′-Dimycolate (Cord Factor) Enhances Neovascularization through Vascular Endothelial Growth Factor Production by Neutrophils and Macrophages

Abstract: Trehalose 6,6-dimycolate (TDM) plays important roles in the development of granulomatous inflammation during infection with Mycobacterium spp., Rhodococcus spp., etc. To reveal the augmenting effect of TDM on vascular endothelial growth factor (VEGF) production and neovascularization, we investigated murine granulomatous tissue air pouches induced by Rhodococcus sp. strain 4306 TDM dissolved in Freund's incomplete adjuvant (FIA), comparing them to pouches treated with FIA alone. Histologically, granulomatous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 31 publications
2
41
1
Order By: Relevance
“…It was also found that a GLB-covering film partly prevents monocyte adhesion to plastic. However, our findings are in controversy with the published results (Sakaguchi et al 2000;Ozeki et al 2006) showing increased TNF-a release by murine neutrophils and macrophages after the incubation in TDM-coated microplates, and with data of Lima et al (2001) showing high cytokine (TNF-a, IL-6, 10, 12, IFN-c) release by murine macrophages incubated in TDM-covered glass coverslips. One possible explanation for the difference between our and other authors' results lies in the fact that cytokine secretion by monocytes is a complex process requiring both cell adhesion and exposure to a chemical inducer such as bacterial antigen or endotoxin (Petit-Bertron et al 2003).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It was also found that a GLB-covering film partly prevents monocyte adhesion to plastic. However, our findings are in controversy with the published results (Sakaguchi et al 2000;Ozeki et al 2006) showing increased TNF-a release by murine neutrophils and macrophages after the incubation in TDM-coated microplates, and with data of Lima et al (2001) showing high cytokine (TNF-a, IL-6, 10, 12, IFN-c) release by murine macrophages incubated in TDM-covered glass coverslips. One possible explanation for the difference between our and other authors' results lies in the fact that cytokine secretion by monocytes is a complex process requiring both cell adhesion and exposure to a chemical inducer such as bacterial antigen or endotoxin (Petit-Bertron et al 2003).…”
Section: Discussioncontrasting
confidence: 99%
“…GLBcoated plates were prepared as described by Sakaguchi et al (2000). Namely, the GLB was dissolved in isopropanol to the concentrations of 1, 10, 100 and 1,000 lg/mL (similar to those used for emulsion preparation), and 100-lL aliquots were placed into wells.…”
Section: Cytokine Production Stimulation Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…10) In this study, it can be certified that SK and shikonin enhance neovascularization in granulomatous tissue formation in the mice air pouch through VEGF produced by infiltrated neutrophils.…”
mentioning
confidence: 97%